PANDANGAN SOSIOLOGI HUKUM ISLAM TERHADAP TRADISI MAPPATOPO PADA JAMA’AH HAJI SUKU BUGIS PERANTAUAN DI KABUPATEN FAKFAK - Nonik Fajariani; Muhammad Maghfurrohman; Miftahul Huda (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2024)
The difference traditions from each region in Indonesia makes them unique and has their own characteristics also. One of them comes from the South Sulawesi area, namely the Mappatoppo tradition. In the application of this tradition, there are several different views, therefore the author will explain how this tradition is seen from the perspective of Islamic law. This research uses the field research method, by collecting data based on the results of observations and interviews with some people. The Mappatopo tradition is a tradition of awarding titles Hajj who carried out by the overseas Bugis community in Fakfak Regency after performing the Hajj pilgrimage. The results of this research show that from the perspective of Islamic law, there are several deviations in the implementation of this Mappatopo tradition, namely the pilgrimage procession carried out by someone strange, the use of songko’ haji (head covering) for women who do not cover their private parts completely, and excessive use of jewelry (gold) and excessive decoration (Tabbaruj). According to the limitation theory of Muhammad Syahrur, there is no prohibition on implementing it as long as it can be applied according to limits that are in accordance with the teachings of the Shari'a, neither more nor less than what has been determined by the Shari'a.